Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Let's solve the given problem step by step.
### Problem Restatement
We have a line given by the equation [tex]\(\frac{x}{a} + \frac{y}{b} = 1\)[/tex], which intersects the [tex]\(x\)[/tex]-axis at point [tex]\(P\)[/tex] and the [tex]\(y\)[/tex]-axis at point [tex]\(Q\)[/tex]. The distances [tex]\(PQ\)[/tex] is [tex]\(\sqrt{45}\)[/tex], and the gradient of the line [tex]\(PQ\)[/tex] is [tex]\(-\frac{1}{2}\)[/tex]. We need to find the values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex].
### Step-by-Step Solution
1. Determine the coordinates of [tex]\(P\)[/tex] and [tex]\(Q\)[/tex]:
- The line meets the [tex]\(x\)[/tex]-axis at [tex]\(P\)[/tex], so set [tex]\(y = 0\)[/tex] in the equation: [tex]\(\frac{x}{a} + \frac{0}{b} = 1 \implies x = a\)[/tex]. Hence, [tex]\(P = (a, 0)\)[/tex].
- The line meets the [tex]\(y\)[/tex]-axis at [tex]\(Q\)[/tex], so set [tex]\(x = 0\)[/tex] in the equation: [tex]\(\frac{0}{a} + \frac{y}{b} = 1 \implies y = b\)[/tex]. Hence, [tex]\(Q = (0, b)\)[/tex].
2. Calculate the distance [tex]\(PQ\)[/tex]:
The distance between [tex]\(P (a, 0)\)[/tex] and [tex]\(Q (0, b)\)[/tex] is given by the distance formula:
[tex]\[ PQ = \sqrt{(a - 0)^2 + (0 - b)^2} = \sqrt{a^2 + b^2} \][/tex]
Given that [tex]\(PQ = \sqrt{45}\)[/tex], we have:
[tex]\[ \sqrt{a^2 + b^2} = \sqrt{45} \][/tex]
Squaring both sides, we get:
[tex]\[ a^2 + b^2 = 45 \][/tex]
3. Determine the gradient of the line [tex]\(PQ\)[/tex]:
The gradient (or slope) of the line passing through [tex]\(P (a, 0)\)[/tex] and [tex]\(Q (0, b)\)[/tex] is:
[tex]\[ \text{Gradient} = \frac{b - 0}{0 - a} = \frac{b}{-a} = -\frac{b}{a} \][/tex]
Given that the gradient is [tex]\(-\frac{1}{2}\)[/tex], we have:
[tex]\[ -\frac{b}{a} = -\frac{1}{2} \][/tex]
Removing the negative signs, this simplifies to:
[tex]\[ \frac{b}{a} = \frac{1}{2} \][/tex]
Solving for [tex]\(b\)[/tex], we get:
[tex]\[ b = \frac{a}{2} \][/tex]
4. Solve the System of Equations:
Now we have two equations:
[tex]\[ a^2 + b^2 = 45 \][/tex]
[tex]\[ b = \frac{a}{2} \][/tex]
Substitute [tex]\(b = \frac{a}{2}\)[/tex] into the first equation:
[tex]\[ a^2 + \left(\frac{a}{2}\right)^2 = 45 \][/tex]
Simplify inside the parentheses:
[tex]\[ a^2 + \frac{a^2}{4} = 45 \][/tex]
Multiply through by 4 to clear the fraction:
[tex]\[ 4a^2 + a^2 = 180 \][/tex]
Combine like terms:
[tex]\[ 5a^2 = 180 \][/tex]
Solve for [tex]\(a^2\)[/tex]:
[tex]\[ a^2 = 36 \][/tex]
Taking the positive square root (since [tex]\(a\)[/tex] and [tex]\(b\)[/tex] are positive):
[tex]\[ a = 6 \][/tex]
Substitute [tex]\(a = 6\)[/tex] back into [tex]\(b = \frac{a}{2}\)[/tex]:
[tex]\[ b = \frac{6}{2} = 3 \][/tex]
### Conclusion
The values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex] are:
[tex]\[ a = 6 \quad \text{and} \quad b = 3 \][/tex]
### Problem Restatement
We have a line given by the equation [tex]\(\frac{x}{a} + \frac{y}{b} = 1\)[/tex], which intersects the [tex]\(x\)[/tex]-axis at point [tex]\(P\)[/tex] and the [tex]\(y\)[/tex]-axis at point [tex]\(Q\)[/tex]. The distances [tex]\(PQ\)[/tex] is [tex]\(\sqrt{45}\)[/tex], and the gradient of the line [tex]\(PQ\)[/tex] is [tex]\(-\frac{1}{2}\)[/tex]. We need to find the values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex].
### Step-by-Step Solution
1. Determine the coordinates of [tex]\(P\)[/tex] and [tex]\(Q\)[/tex]:
- The line meets the [tex]\(x\)[/tex]-axis at [tex]\(P\)[/tex], so set [tex]\(y = 0\)[/tex] in the equation: [tex]\(\frac{x}{a} + \frac{0}{b} = 1 \implies x = a\)[/tex]. Hence, [tex]\(P = (a, 0)\)[/tex].
- The line meets the [tex]\(y\)[/tex]-axis at [tex]\(Q\)[/tex], so set [tex]\(x = 0\)[/tex] in the equation: [tex]\(\frac{0}{a} + \frac{y}{b} = 1 \implies y = b\)[/tex]. Hence, [tex]\(Q = (0, b)\)[/tex].
2. Calculate the distance [tex]\(PQ\)[/tex]:
The distance between [tex]\(P (a, 0)\)[/tex] and [tex]\(Q (0, b)\)[/tex] is given by the distance formula:
[tex]\[ PQ = \sqrt{(a - 0)^2 + (0 - b)^2} = \sqrt{a^2 + b^2} \][/tex]
Given that [tex]\(PQ = \sqrt{45}\)[/tex], we have:
[tex]\[ \sqrt{a^2 + b^2} = \sqrt{45} \][/tex]
Squaring both sides, we get:
[tex]\[ a^2 + b^2 = 45 \][/tex]
3. Determine the gradient of the line [tex]\(PQ\)[/tex]:
The gradient (or slope) of the line passing through [tex]\(P (a, 0)\)[/tex] and [tex]\(Q (0, b)\)[/tex] is:
[tex]\[ \text{Gradient} = \frac{b - 0}{0 - a} = \frac{b}{-a} = -\frac{b}{a} \][/tex]
Given that the gradient is [tex]\(-\frac{1}{2}\)[/tex], we have:
[tex]\[ -\frac{b}{a} = -\frac{1}{2} \][/tex]
Removing the negative signs, this simplifies to:
[tex]\[ \frac{b}{a} = \frac{1}{2} \][/tex]
Solving for [tex]\(b\)[/tex], we get:
[tex]\[ b = \frac{a}{2} \][/tex]
4. Solve the System of Equations:
Now we have two equations:
[tex]\[ a^2 + b^2 = 45 \][/tex]
[tex]\[ b = \frac{a}{2} \][/tex]
Substitute [tex]\(b = \frac{a}{2}\)[/tex] into the first equation:
[tex]\[ a^2 + \left(\frac{a}{2}\right)^2 = 45 \][/tex]
Simplify inside the parentheses:
[tex]\[ a^2 + \frac{a^2}{4} = 45 \][/tex]
Multiply through by 4 to clear the fraction:
[tex]\[ 4a^2 + a^2 = 180 \][/tex]
Combine like terms:
[tex]\[ 5a^2 = 180 \][/tex]
Solve for [tex]\(a^2\)[/tex]:
[tex]\[ a^2 = 36 \][/tex]
Taking the positive square root (since [tex]\(a\)[/tex] and [tex]\(b\)[/tex] are positive):
[tex]\[ a = 6 \][/tex]
Substitute [tex]\(a = 6\)[/tex] back into [tex]\(b = \frac{a}{2}\)[/tex]:
[tex]\[ b = \frac{6}{2} = 3 \][/tex]
### Conclusion
The values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex] are:
[tex]\[ a = 6 \quad \text{and} \quad b = 3 \][/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.